A simplified error estimator for the CB method and its application to error control. (February 2016) - Boo, Seung-Hwan; Kim, Jin-Gyun; Lee, Phill-Seung
Highlights: We propose a simplified error estimator for the Craig–Bampton method. Computational cost is significantly reduced with negligible accuracy loss. The contribution of a specific substructure to an eigenvalue error can be estimated. The computational efficiency and an error control strategy are demonstrated. Abstract: In this paper, we simplify the error estimation technique developed for the Craig–Bampton (CB) method (Kim et al., 2014). The original formulation is simplified by neglecting insignificant terms, a new error estimator is obtained, and thus computational cost is significantly reduced with negligible accuracy loss. In addition, the contribution of a specific substructure to a relative eigenvalue error can be estimated using the new formulation, in which the estimated relative eigenvalue error is represented by a simple summation of the substructural errors estimated. Therefore, the new formulation can be employed for error control by using the detailed errors estimated for a certain substructure. Through various numerical examples, we verify the accuracy and computational efficiency of the new formulation, and demonstrate an error control strategy.